Cost-effective reductions of PM2.5 concentrations and exposure in Italy. (September 2016) - Ciucci, A.; D'Elia, I.; Wagner, F.; Sander, R.; Ciancarella, L.; Zanini, G.; Schöpp, W.
Abstract: In recent years several European air pollution policies have been based on a cost-effectiveness approach. In the European Union, the European Commission starts using the multi-pollutant, multi-effect GAINS (Greenhouse Gas Air Pollution Interactions and Synergies) model to identify cost-effective National Emission Ceilings and specific emission control measures for each Member State to reach these targets. In this paper, we apply the GAINS methodology to the case of Italy with 20 subnational regions. We present regional results for different approaches to environmental target setting for PM2.5 pollution in the year 2030. We have obtained these results using optimization techniques consistent with those of GAINS-Europe, but at a higher resolution. Our results show that an overall health-impact oriented approach is more cost-effective than setting a nation-wide limit value on ambient air quality, such as the one set for the year 2030 by the European Directive on ambient air quality and cleaner air for Europe. The health-impact oriented approach implies additional emission control costs of 153 million €/yr on top of the baseline costs, compared to 322 million €/yr for attaining the nation-wide air quality limit. We provide insights into the distribution of costs and benefits for regions within Italy and identify the main beneficiaries of a health-impact approach over a limit-value approach. Highlights: The GAINS cost-optimization methodology has been applied to the Italian territory. Different environmental target setting approaches have been compared. A regulatory approach focusing on health impacts rather than on air quality is more cost-effective. Distribution of costs and benefits for the 20 Italian regions are presented.